2021
DOI: 10.1073/pnas.2102775118
|View full text |Cite
|
Sign up to set email alerts
|

Scalable live-attenuated SARS-CoV-2 vaccine candidate demonstrates preclinical safety and efficacy

Abstract: Successfully combating the COVID-19 pandemic depends on mass vaccination with suitable vaccines to achieve herd immunity. Here, we describe COVI-VAC, the only live attenuated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine currently in clinical development. COVI-VAC was developed by recoding a segment of the viral spike protein with synonymous suboptimal codon pairs (codon-pair deoptimization), thereby introducing 283 silent (point) mutations. In addition, the furin cleavage site within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(117 citation statements)
references
References 41 publications
(65 reference statements)
3
106
0
1
Order By: Relevance
“…Hamsters, particularly Syrian golden hamsters, are the most promising pre-clinical model of SARS-CoV-2 due to their consistent clinical signs and ability to transmit the virus to other hamsters, combined with their relative ease of housing and handling in biocontainment facilities. Syrian golden hamsters have already been used extensively to gain insights into the basic science of SARS-CoV-2 pathogenesis [ 156 , 157 , 158 , 159 , 160 , 161 ] and to test therapeutic interventions [ 162 , 163 , 164 , 165 , 166 , 167 ] and vaccines [ 168 , 169 , 170 , 171 , 172 ]. Moreover, there is clear evidence that older Syrian golden hamsters and Roborovski hamsters develop respiratory disease and lung pathology that recapitulates the severe disease found in older COVID-19 patients, and therefore could be highly informative models [ 77 , 81 ].…”
Section: Main Textmentioning
confidence: 99%
“…Hamsters, particularly Syrian golden hamsters, are the most promising pre-clinical model of SARS-CoV-2 due to their consistent clinical signs and ability to transmit the virus to other hamsters, combined with their relative ease of housing and handling in biocontainment facilities. Syrian golden hamsters have already been used extensively to gain insights into the basic science of SARS-CoV-2 pathogenesis [ 156 , 157 , 158 , 159 , 160 , 161 ] and to test therapeutic interventions [ 162 , 163 , 164 , 165 , 166 , 167 ] and vaccines [ 168 , 169 , 170 , 171 , 172 ]. Moreover, there is clear evidence that older Syrian golden hamsters and Roborovski hamsters develop respiratory disease and lung pathology that recapitulates the severe disease found in older COVID-19 patients, and therefore could be highly informative models [ 77 , 81 ].…”
Section: Main Textmentioning
confidence: 99%
“…9 ). 14 History has demonstrated that all types of vaccines can be safe or dangerous and that strict animal experiments and clinical trials can differentiate between safe vaccines and dangerous vaccines. 9 For example, clinical trials revealed the severe ADE effect of the inactivated vaccine FI-RSV for respiratory syncytial virus and the adenovirus vector vaccine for human immunodeficiency virus.…”
Section: Disadvantages Of Lavs and Solutionsmentioning
confidence: 99%
“…Furthermore, immunosorbent assay (ELISA) was carried out to measure IgG titers against SARS-CoV-2 spike S1 in hamsters inoculated with WT WA1 or COVI-VAC. A strong anti-spike S1 antibody response was induced, and high levels of neutralizing antibodies were determined in COVI-VAC-inoculated hamsters [67]. In December 2020 a Phase I clinical trial of COVI-VAC was commenced by Codagenix and the Serum Institute of India.…”
Section: Covi-vacmentioning
confidence: 99%